Sustainability, Green Innovation, dan Green Innovation Costing dalam Peningkatan Nilai Perusahaan: Tinjauan Literatur (2014-2025) - Lola Putri Wulandari (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Increasing regulatory pressure, investor expectations, and environmental risks have pushed firms to embed sustainability concerns into business strategy. Green innovation and sustainability/ESG practices are often framed as potential sources of competitive advantage and risk mitigation. However, empirical evidence on their value relevance remains mixed, particularly in emerging markets. This paper provides a focused/scoping literature review of peer-reviewed studies published between 2014 and 2025 examining the links between sustainability/ESG, green innovation, eco-efficiency, environmental performance, environmental and carbon disclosure, and firm performance/value. Importantly, the review highlights Environmental Management Accounting (EMA), Activity-Based Costing (ABC), and the broader concept of green innovation costing as internal mechanisms that enable firms to identify, allocate, and control green-related costs. A thematic synthesis yields three recurring insights. First, green innovation and sustainability/ESG practices tend to be positively associated with firm performance and value, yet the relationship is frequently contingent on time-lag dynamics and innovation type (pollution prevention versus pollution control). Second, environmental transparency works as a signaling and legitimacy channel that helps stakeholders assess the credibility of green initiatives, although the effect may weaken when disclosure quality is low or capital markets pay limited attention. Third, costing and environmental management information systems (EMA/ABC) repeatedly emerge as key explanatory mechanisms for heterogeneous findings across studies: green initiatives are more likely to create value when their costs and benefits are measurable, managed, and auditable. The paper proposes an integrative conceptual framework and a forward-looking research agenda emphasizing stronger measurement of green innovation costing, more causal research designs, and clearer separation between short- and long-run effects. Practical implications point to the need for integrating EMA/ABC into managerial decisions, improving disclosure quality, and aligning internal controls with market expectations.